2023
DOI: 10.1038/s41392-023-01479-4
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a Toll-like receptor 2/6 agonist potentiates mRNA vaccines against cancer and infectious diseases

Abstract: AbstractmRNA vaccines have emerged rapidly in recent years as a prophylactic and therapeutic agent against various diseases including cancer and infectious diseases. Improvements of mRNA vaccines have been underway, among which boosting of efficacy is of great importance. Pam2Cys, a simple synthetic metabolizable lipoamino acid that signals through Toll-like receptor (TLR) 2/6 pathway, eliciting both humoral and cellular adaptive immune responses, is an interesting candidate adjuvant. To investigate the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…reported that LNPs utilizing MC3 lipid incorporated with 3% Tween 20, a surfactant with a branched PEG chain linked to a short lipid tail, performed much stronger and specific transfection of pDNA at the LNs than those mixed with Tween 80. 76 Also, Pam2Cys, a simple synthetic metabolizable lipoamino acid that signals through the Toll-like receptor (TLR) 2/6 pathway as a candidate adjuvant capable of eliciting an adaptive immune response, 78 , 79 was incorporated by Huashan Shi and colleagues into the mRNA-LNPs vaccine ( Figure 3 A). Utilizing intramuscular administration, their findings demonstrated that Pam2Cys-LNPs (pm vaccine) resulted in an effective immune milieu in the draining lymph nodes (dLNs) through antigen presentation accomplished primarily by migratory and dLN-resident conventional type 2 DCs (cDC2s), which triggered both CD4 + and CD8 + T cell responses, and induction of IL-12 and IL-17, among other cytokines in the mice model ( Figure 3 B).…”
Section: Organ-selective Lnps As Delivery Platforms For Nucleic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that LNPs utilizing MC3 lipid incorporated with 3% Tween 20, a surfactant with a branched PEG chain linked to a short lipid tail, performed much stronger and specific transfection of pDNA at the LNs than those mixed with Tween 80. 76 Also, Pam2Cys, a simple synthetic metabolizable lipoamino acid that signals through the Toll-like receptor (TLR) 2/6 pathway as a candidate adjuvant capable of eliciting an adaptive immune response, 78 , 79 was incorporated by Huashan Shi and colleagues into the mRNA-LNPs vaccine ( Figure 3 A). Utilizing intramuscular administration, their findings demonstrated that Pam2Cys-LNPs (pm vaccine) resulted in an effective immune milieu in the draining lymph nodes (dLNs) through antigen presentation accomplished primarily by migratory and dLN-resident conventional type 2 DCs (cDC2s), which triggered both CD4 + and CD8 + T cell responses, and induction of IL-12 and IL-17, among other cytokines in the mice model ( Figure 3 B).…”
Section: Organ-selective Lnps As Delivery Platforms For Nucleic Acidsmentioning
confidence: 99%
“…Utilizing intramuscular administration, their findings demonstrated that Pam2Cys-LNPs (pm vaccine) resulted in an effective immune milieu in the draining lymph nodes (dLNs) through antigen presentation accomplished primarily by migratory and dLN-resident conventional type 2 DCs (cDC2s), which triggered both CD4 + and CD8 + T cell responses, and induction of IL-12 and IL-17, among other cytokines in the mice model ( Figure 3 B). 79
Figure 3 Strategies for lymph node-targeted LNPs (A) Preparation of Pam2Cys-incorporated mRNA vaccines. (B) Mechanism of action for Pam2Cys-incorporated mRNA vaccines.
…”
Section: Organ-selective Lnps As Delivery Platforms For Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“… Category Technologies Target pathways Applications Ref. Co-administration of adjuvants GM-CSF - Renal cell cancer [ 64 ] Fms-like tyrosine kinase 3 (FLT3) ligand FLT3 (DC activation) Melanoma [ 65 ] R848 TLR7 Influenza virus [ 66 ] Lipid nanoparticles encapsulating hydrophilic adjuvants iLNP encapsulating manganese STING SARS-CoV-2 [ 67 ] PLGA-core/lipid shell nanoparticles containing gardiquimod TLR7 Cancer (model antigen) [ 68 ] Lipid nanoparticles containing hydrophobic adjuvants Lipid conjugated with R848 TLR7, 8 Cancer (model antigen) [ 69 ] iLNP containing Pam2Cys TLR2/6 Colon cancer, SARS-CoV-2 [ 70 ] Lipid carriers containing α-galactosylceramide iNKT cell activation Cancer (model antigen) [ 71 ] Malaria [ 72 ] Melanoma [ 73 ] Monophosphoryl lipid A …”
Section: Adjuvanticitymentioning
confidence: 99%
“…Lipid nanoparticle (LNP)-based mRNA vaccine has achieved great success during the COVID-19 pandemic and accelerated its application on various infectious diseases. On the other hand, urgent approval for COVID-19 suggests a requirement for the optimization of lipid nanoparticles for vaccine applications, especially on its immunogenicity. Recent studies reported toll-like receptor agonist (TLRα)-incorporated lipid nanoparticles for the improved immunogenicity of peptide and mRNA vaccines with enhanced cellular and humoral immune responses against the antigens, which consequently broadens the range of protection to the variant of concerns (VOCs). Stimulator of interferon genes (STING) agonist-derived lipid and other lipid structures were also developed to improve the mRNA vaccination effect. , However, TLR-agonist and STING-pathway trigger vast inflammatory responses to immune cells, and these strategies could induce undesirable adverse events in vaccinee, and alternative strategies are on demand. Microbiomes, the microbes in the host organism, have been known for their diverse role in the host immune system and are associated with various human diseases from cancers to inflammatory diseases .…”
mentioning
confidence: 99%